Financial Services and Arrangements to Facilitate the (Ex)Portability of Social Security Benefits in the Southern African Development Community - Mpedi, Letlhokwa George (Potchefstroom Electronic Law Journal, 2022)
This contribution reviews the financial services and arrangements to facilitate the (ex)portability of social security benefits in the Southern African Development Community (the SADC). It commences by providing a general background to the theme it covers by focussing on the (ex)portability of social security as part of the coordination principles contained in the pertinent International Labour Organisation social security conventions, the (ex)portability of social security benefits provided for in SADC social security instruments, the key purpose of the payment of social security abroad, and the negative impact of the absence of the suitable cross-border payment of benefits in the SADC. It proceeds by discussing the common methods used for the cross-border payment of social security benefits in the SADC. These models are business-to-business, business-to-client, government institution-to-government institution, and client-to-business. The contribution continues by reviewing selected challenges in the region facing financial services and arrangements to facilitate the payment of social security abroad. These challenges are the lack of a single currency, remittance costs, and unbanked persons. The paper concludes by making recommendations for developing a coherent regional and enabling framework for the payment of social security benefits abroad.